Engineering Mechanics: Statics and Dynamics - Gray Gary L (Mc Graw Hill Higher Education, 2010)
Plesha, Gray, and Costanzo’s Engineering Mechanics: Statics & Dynamics presents the fundamental concepts clearly, in a modern context using applications and pedagogical devices that connect with today’s students.